Evaluation of residential sprinkler system in the Klang Valley - Thin, Voon Tuck (1999)
Fire awareness in residential units m Malaysia remams low compared to developed countries. Fire safety awareness is not improved through campaigns not other methods, and as such, is expected to remain low. This study aims to gauge the level of fire safety awareness through a survey in the Klang Valley. In addition, the main focus of study is on the effectiveness of residential sprinkler systems and how these systems can be implemented in Malaysia. A specific design will be effected for the HRC housing project undertaken by Universiti Putra Malaysia. The study has concluded that fire safety awareness in residential units m Malaysia. This is based on the incidences of smoke detector usage, sprinkler system usage and evacuation plans in the event of fires. Both smoke detector usage and sprinkler systems in residential units are proven to reduce the fatality rate when a fire does break out. As such, implementation of these systems can significantly improve the life safety from fire of Malaysian homes. Unfortunately, the costs of fire protection systems in Malaysia can be prohibitive, and potential cost savings from reduction m insurance premiums are unlikely to be able to offset the initial investment required. The design developed for the HRC houses to be built by Universiti Putra Malaysia can incorporate residential sprinklers and smoke detectors to improve fire safety. Realisation of the entire fire strategy and design concept is however not done yet, especially as to the siting of the water storage requirements.